Rancang Bangun Pemantau Suhu dan Kelembapan di Kota Depok dengan Metode Fuzzy Logic Berbasis Arduino - Pratama, Wildan Ikbar; Andrianingsih (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the current era, development occurs very rapidly. Global warming is something that has just been heard a few years ago. This has an impact on human life, especially in urban areas. UHI is part of the temperature rise phenomenon that occurs in urban areas and is caused by isolated locations (different conditions) that have higher surface or air temperatures than the surrounding areas in measurements using an Arduino device. UHI has a negative impact because it causes changes in air quality and affects human health, energy use, and climate change. This research aims to build a temperature and humidity measurement system that analyzes UHI. The research parameters used were temperature and humidity. This research uses the fuzzy logic method. This study has an absolute error value of ± 1 oC.